1989
DOI: 10.1007/bf02554726
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study for preoperative staging of rectal cancer

Abstract: A comparative study of preoperative evaluation of rectal cancer is presented. Sixty-eight patients with rectal cancer were examined digitally and by computerized tomography and transrectal ultrasound. Preoperative staging was compared with pathologic findings at surgery. Digital examination and transrectal ultrasound were accurate in 82.8 and 76.2 percent, respectively and were superior to CT, which was accurate in 65.5 percent of cases for assessment of rectal wall invasion. All three modes play a role in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 13 publications
2
14
0
3
Order By: Relevance
“…For instance, with CT technique correct analysis of tumors confined to the rectal wall or with moderate perirectal spread has been questioned as this technique affords little possibility of identifying the different layers of the rectal wall [14-171. Our results showed that TRUS was clearly superior to CT in staging local tumor growth in the lower two thirds of the rectum. The high rate of prediction of growth beyond the rectal wall with ultrasound corresponds well with figures presented in other reports [15,17,18]. These findings indicate that ultrasound can be of importance in the identification of those tumors with perirectal growth for which radiotherapy could be suitable.…”
Section: Discussionsupporting
confidence: 77%
“…For instance, with CT technique correct analysis of tumors confined to the rectal wall or with moderate perirectal spread has been questioned as this technique affords little possibility of identifying the different layers of the rectal wall [14-171. Our results showed that TRUS was clearly superior to CT in staging local tumor growth in the lower two thirds of the rectum. The high rate of prediction of growth beyond the rectal wall with ultrasound corresponds well with figures presented in other reports [15,17,18]. These findings indicate that ultrasound can be of importance in the identification of those tumors with perirectal growth for which radiotherapy could be suitable.…”
Section: Discussionsupporting
confidence: 77%
“…The limited ability to identify nodal involvement preoperatively is problematic. Techniques such as endorectal ultrasound and MRI using endorectal coils are among the most sensitive methods (70-90% accurate) for determining the preoperative staging of the tumor, and hence should probably be used routinely [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Karzinom waren die Ergebnisse für das CS II nicht zuverlässig. Waizer et al [28] gaben für Dukes-A-Karzinome eine vergleichbare Sensitivität der rektalen Untersuchung von 85,7% und Nicholls et al [20,21] …”
Section: Rektale Untersuchungunclassified